2013
DOI: 10.1177/1071100713477621
|View full text |Cite
|
Sign up to set email alerts
|

Achilles Tendon Injuries in a United States Population

Abstract: In this study, sports participation was the most common mechanism, but not to the same extent seen in the European or US military studies. Basketball was the most commonly involved sport, as compared to soccer in Europe. Age and BMI had a directly proportional correlation with time to diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
167
2
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(188 citation statements)
references
References 30 publications
11
167
2
8
Order By: Relevance
“…Prodromal symptoms are a common finding in the patient's history, especially the elite athlete [10,11]. Older patients and patients with a body mass index greater than 30 were more likely to be injured in nonsporting activities, and were also more likely to have a missed diagnosis for their injury [5]. Furthermore, a study investigating Achilles tendon ruptures in women agreed with previous reports that acute Achilles rupture is more common in men.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Prodromal symptoms are a common finding in the patient's history, especially the elite athlete [10,11]. Older patients and patients with a body mass index greater than 30 were more likely to be injured in nonsporting activities, and were also more likely to have a missed diagnosis for their injury [5]. Furthermore, a study investigating Achilles tendon ruptures in women agreed with previous reports that acute Achilles rupture is more common in men.…”
Section: Introductionsupporting
confidence: 79%
“…The injury occurs during a strong dorsiflexion force that is applied to the ankle as the gastrocnemius-soleus complex simultaneously contracts to plantarflex the ankle: an eccentric contraction. Recently, a study investigating the general population of the United States population found that basketball was the most commonly involved sport, accounting for 48 % of all ruptures [5]. In Canada and Europe, soccer accounted for most of the traumatic tendon ruptures [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] En la actualidad, no existe un único método para la reparación, por lo que la mayoría de los cirujanos se basan en su experiencia y preferencia personales. 5,11,[15][16][17] El hilo y la técnica de sutura deberían garantizar la aproximación y el cierre de la diástasis tendinosa (brecha) hasta la curación total del tendón.…”
Section: Discussionunclassified
“…14,20 La sutura que se utilizaba inicialmente fue criticada, porque proporcionaba alrededor del 50% de la resistencia comparada con la reparación abierta. 8 La técnica percutánea presentaba un elevado riesgo de lesión del nervio sural (hasta del 60%) 8,12 y la tasa de una nueva rotura era elevada (6,4%). 11 Klein y cols.…”
Section: Discussionunclassified
“…3,16,29 El "weekend warrior" se define como una persona de mediana edad que realiza esfuerzos atléticos y deportivos de manera ocasional y que, según se demostró, presenta un mayor riesgo de lesionarse el tendón de Aquiles. 30 no existe un acuerdo universal y la bibliografía no es clara sobre el tratamiento ideal para la rotura aguda del tendón de Aquiles. 11,12,16,27,31 Khan y cols.…”
Section: Discussionunclassified